STRATEGI PEMBELAJARAN TATAP MUKA TERBATAS (PTMT) PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA SISWA KELAS VI DI SD NEGERI 2 NYITDAH KECAMATAN KEDIRI KABUPATEN TABANAN - I Made Sugiarta; I Gede Widya Suksma; Ni Nyoman Ayu Cahyani Putri (UNHI PRESS, 2022)
The Tabanan Regency Government through the Education and Culture Office regarding the implementation of face-to-face learning in education units within the Tabanan Regency Education and Culture Office, decided that the teaching and learning process (KBM) at the PAUD, SD and SMP level education units uses the Limited Face-to-face Learning (PTMT) method. The problems in this paper include: (1) Why is a Limited Face-to-face Learning (PTMT) strategy needed for Hindu Religion and Moral Education for Class VI Students at SD Negeri 2 Nyitdah, Kediri District, Tabanan Regency?, (2) How is the process of implementing the Learning strategy? Limited Face-to-Face (PTMT) Hindu Religious Education and Character Education for Class VI Students at SD Negeri 2 Nyitdah, Kediri District, Tabanan Regency?, (3) Supporting factors and inhibiting factors for implementing the Limited Face-to-face Learning (PTMT) strategy for Hindu Religious Education in Class VI students at SD Negeri 2 Nyitdah, Kediri District, Tabanan Regency. This type of research is a type of qualitative research that uses no-participant observation techniques, in-depth interviews, document studies as research methods. The conclusions are: (1) To avoid falling behind in learning, it is easier for teachers to provide material, and the material is more easily absorbed by students. (2) Establishing study sessions, implementing the covid-19 process, and using Small Group Discussion strategies and Active Learning strategies. (3) Supporting factors: Circular (SKB) 4 Ministers, facilities and infrastructure. Inhibiting factor: Parents are doubtful, and the subjects are taken to the core. ABSTRAK Pemerintah Kabupaten Tabanan melalui Dinas Pendidikan dan Kebudayaan tentang pelaksanaan pembelajaran tatap muka satuan pendidikan di lingkungan Dinas Pendidikan dan Kebudayaan Kabupaten Tabanan, memutuskan bahwa proses Kegiatan Belajar Mengajar (KBM) pada satuan pendidikan tingkat PAUD, SD dan SMP menggunakan metode Pembelajaran Tatap Muka Terbatas (PTMT). Masalah pada penulisan ini meliputi: (1) Mengapa diperlukan strategi Pembelajaran Tatap Muka Terbatas (PTMT) Pendidikan Agama Hindu dan Budi Pekerti pada Siswa Kelas VI di SD Negeri 2 Nyitdah, Kecamatan Kediri, Kabupaten Tabanan?, (2) Bagaimanakah proses pelaksanaan strategi Pembelajaran Tatap Muka Terbatas (PTMT) Pendidikan Agama Hindu dan Budi Pekerti pada Siswa Kelas VI di SD Negeri 2 Nyitdah, Kecamatan Kediri, Kabupaten Tabanan?, (3) Faktor pendukungdan faktor penghambat pelaksanaan strategi Pembelajaran Tatap Muka Terbatas (PTMT) Pendidikan Agama Hindu pada Siswa Kelas VI di SD Negeri 2 Nyitdah, Kecamatan Kediri, Kabupaten Tabanan. Jenis penelitian ini merupakan jenis penelitian kualitatif yang menggunakan teknik observasi no-partisipan, wawancara mendalam, studi dokumen sebagai metode penelitian. Adapun kesimpulannya: (1) Untuk menghindari terjadinya ketertinggalan belajar, memudahkan guru memberikan materi, dan materi lebih mudah diserap peserta didik. (2) Membentuk sesi belajar, Menerapkan prokes covid-19, dan penggunaan strategi pembelajaran Kelompok Kecil (Small Group Discussion) dan strategi Active Learning. (3) Faktor pendukung: Surat Edaran (SKB) 4 Menteri, sarana dan prasarana. Faktor penghambat : Orang Tua yang ragu, dan mata pelajaran diambil inti-intinya saja.